2018
DOI: 10.5539/gjhs.v10n9p103
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Smoking and Alcohol Consumption among Street Vendors in the Metropolitan Area of Bucaramanga, Colombia

Abstract: AIM: The objective of the study was to characterize, learn and establish related factors about the behavior of alcohol and tobacco consumption in a sample of street vendors in the Metropolitan Area of Bucaramanga, Colombia.METHODS: A descriptive cross-sectional study was conducted on 425 street vendors. With regard to sampling, a non-probability sampling was conducted on the streets of every city in the Metropolitan Area. Each worker was given a questionnaire that included socio-demographic and occupational va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Tobacco use, both in smoke and smokeless mode, is a cause of concern among South Asian communities living in the Western World (Khaja et al, 2016). Another study from Colombia reported that smokers had a higher inclination to get involved in harmful alcohol consumption (Amaya, 2018). (TPB) (Topa & Moriano, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco use, both in smoke and smokeless mode, is a cause of concern among South Asian communities living in the Western World (Khaja et al, 2016). Another study from Colombia reported that smokers had a higher inclination to get involved in harmful alcohol consumption (Amaya, 2018). (TPB) (Topa & Moriano, 2010).…”
Section: Introductionmentioning
confidence: 99%